2012
DOI: 10.1097/jto.0b013e318260de75
|View full text |Cite
|
Sign up to set email alerts
|

Topotecan/Cisplatin Compared with Cisplatin/Etoposide as First-Line Treatment for Patients with Extensive Disease Small-Cell Lung Cancer: Final Results of a Randomized Phase III Trial

Abstract: TP is noninferior to PE in overall survival and superior in time to progression and overall response rates. Because of slightly worse toxicity profile TP is not a first-line standard treatment for patients with extensive disease small-cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…Life expectancy was shortened by .10 years among the current smokers compared with those who had never smoked. Adults who had quit smoking [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] or 45-54 years of age gained approximately 10, 9 and 6 years of life, respectively, compared with those who continued to smoke. This is in complete agreement with the UK observation.…”
mentioning
confidence: 99%
“…Life expectancy was shortened by .10 years among the current smokers compared with those who had never smoked. Adults who had quit smoking [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] or 45-54 years of age gained approximately 10, 9 and 6 years of life, respectively, compared with those who continued to smoke. This is in complete agreement with the UK observation.…”
mentioning
confidence: 99%
“…However, even those with an increase in tumour size after the first course had a median overall survival of 19.9 months, which is much longer than in extended disease (typically 8-12 months) [27,28]. It is, however, possible that an early response assessment as described herein might be used for randomisation or stratification in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The OS of patients with ED-SCLC enrolled in phase III trials has not improved significantly over the last few years (17). Recent phase III trials investigating ED-SCLC (3,10,11,(18)(19)(20) revealed a median OS of ~9-11 months, regardless of the treatment options. Lara et al (11) reported a pivotal trial including 651 patients comparing the efficacy of EP and IP as first-line treatment for patients with ED-SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 327 patients were assigned to the EP arm, exhibiting a median PFS of 5.2 months and a median OS of 9.1 months. Fink et al (18) evaluated the efficacy of EP and topotecan/cisplatin as first-line treatment for patients with ED-SCLC. The EP arm included 345 patients with a median time-to-progression of 5.7 months and a median OS of 9.5 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation